Organizational Interoperability: A Systematic Mapping Study - Proencia, Edlane Cristine dos Santos; Mascarenhas, Ana Patrícia Fontes Magalhães; Mane, Babacar; Claro, Daniela Barreiro; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Organizational interoperability enables collaboration amomg organizations with different structures and processes, promoting efficiency and integration in sectors such as public administration, health, and education. Problem: Implementing organizational interoperability presents significant challenges, including the lack of commonly accepted processes, difficulties interpreting administrative procedures and legislation, and the absence of conceptual models to define inter-organizational relationships. There are few studies that report organizational interoperability, and there is no consensus on several concepts and structures. Solution: The study maps existing approaches, including models for assessing organizational interoperability maturity, and a conceptual model based on Systems of Information Systems (SoIS) to help create interoperability connections between organizations. Information systems theory: Organizational interoperability research is associated with organizational information processing theory. Method: A systematic literature mapping was conducted in databases such as IEEE Xplore, ACM Digital Library, ScienceDirect, and Scopus. Summary of Results: Ten main studies were identified. In general, organizational interoperability has been treated as the ability of organizations to align business processes and expectations for effective information exchange. Challenges include the need for standardized processes, difficulties with regulations, and the absence of conceptual models. Solutions involve process-oriented approaches, but adoption still needs to be improved. Contributions and Impact in the area of information systems: The study contributes by providing a comprehensive view of organizational interoperability, identifying gaps, challenges, and possible solutions. It reinforces the importance of interoperability for inter-organizational collaboration to promote a more efficient and collaborative environment.